The historically enduring gap in death penalty support : re-examining the role of context in the recent history of the black-white divide - Porter, Jeremy R. (Array, 2018)
This paper evaluates four racial‑ecological theories regarding the historically enduring racial divide in public opinion regarding death penalty support. Using geo‑coded data from the 20th century, this research examines the relative representation of African Americans, the level of black‑white economic inequality, and the extent of racial residential segregation on race‑spe‑ cific odds of supporting the death penalty. The research finds support for aspects of racial social context accounting for a portion of the black-white gap in death penalty support at the time. We find differential effects, by race, of representation and segregation as mediators of public opinion regarding the death penalty.